Effect of the Spray Amino Acids and Drip Irrigation Depth on Growth and Yield of Egg Plant (Solanum melongena L.) - Jaafer, Hayder Sadaq (Journal of Kerbala for Agricultural Sciences, 2018)
An experiment was conducted in a plastic house in Horticulture and Forestry Department belongs Al-Najaf Agricultural Directorate during the growing seasons of 2015-2016. The aim was to study the effect of the spray amino acids and irrigation depth on growth and yield of egg plant (Solanum melongena L.). The experiment had comprised twelve treatments; three concentrations (0 and 2 and 4) ml.L-1 of amino acids and four depth of water applications surface drip irrigation D0 and sub-surface at depth of 4 and 8 and 12 cm namely D4 and D8 and D12, respectively. Variations between the means were tested according to Duncan's Multiple Range (D.M.R.) at probability of 0.05. Results showed that spraying with amino acids or add irrigation water with different depths improved vegetative growth (plant height and leaf area and dry root weight and total vegetative dry weight), and total yield. Interaction amino acid spraying with 4 ml.L-1 with treatment of depth 4 cm gave the highest values compared with the interaction treatment of control with treatment of depth 12 cm which gave the lowest values.